PENINGKATAN KEMAMPUAN PASSING DAN SMASH BOLA VOLI DENGAN MODIFIKASI ALAT BANTU DI SDN KEMAYORAN 01 BANGKALAN - Hoddin, Sholeh; Handayani, Heni Yuli; Widodo, Haryo Mukti (JURNAL ILMU KEOLAHRAGAAN, 2025)
The purpose of this study was to determine the effect of the use of assistive devices on improving volleyball passing and smashing. The type of quantitative research case study. The technique used is participant observation. The research instrument is in the form of observation sheets and documentation. The results of the study based on the results of data analysis showed that the ability of students to pass in the assessment based on the initial stage was in the "very good" category, namely 87.5; the acceptance rate of the "very good" category was 87.5; and at the final stage the category "very good" was 85. Meanwhile, in smashing, students in the assessment based on the initial stage were in the "very good" category, namely 89.2; the acceptance rate of the "very good" category was 92.5; and at the final stage the category "very good" was 93.3. Thus, there was an increase in the ability of volleyball passing and smashing with modification of assistive devices at SDN Kemayoran 01 Bangkalan.